2002
DOI: 10.1063/1.1467983
|View full text |Cite
|
Sign up to set email alerts
|

Quasiregular quantum-dot-like structure formation with postgrowth thermal annealing of InGaN/GaN quantum wells

Abstract: Postgrowth thermal annealing of an InGaN/GaN quantum-well sample with a medium level of nominal indium content ͑19%͒ was conducted. From the analyses of high-resolution transmission electron microscopy and energy filter transmission electron microscopy, it was found that thermal annealing at 900 °C led to a quasiregular quantum-dot-like structure. However, such a structure was destroyed when the annealing temperature was raised to 950 °C. Temperature-dependent photoluminescence ͑PL͒ measurements showed quite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…5(a). Several studies have reported that the indium composition in InGaN/GaN MQWs changed as a result of thermal annealing [23], and the thickness of the quantum wells and barriers is also influenced by a hightemperature heat treatment [24]. Moreover, the line-width narrowing was observed due to the enhanced interdiffusion between the dot-like structures and the surrounding indium-deficient matrices by thermal annealing [25].…”
Section: Effect Of Growth Temperature Of P-gan On the Structure Of Mqwsmentioning
confidence: 96%
“…5(a). Several studies have reported that the indium composition in InGaN/GaN MQWs changed as a result of thermal annealing [23], and the thickness of the quantum wells and barriers is also influenced by a hightemperature heat treatment [24]. Moreover, the line-width narrowing was observed due to the enhanced interdiffusion between the dot-like structures and the surrounding indium-deficient matrices by thermal annealing [25].…”
Section: Effect Of Growth Temperature Of P-gan On the Structure Of Mqwsmentioning
confidence: 96%
“…To release strain energy, indium aggregation and phase separation can usually result in nano-scale indium-rich clusters and compositional fluctuations [4][5][6]. In particular, when a perturbation is introduced, such as thermal annealing, spinodal decomposition will enhance the clustering process [7,8]. Besides the local aggregation phenomenon, a more global behavior, called indium pulling [9][10][11], was also discovered.…”
Section: Introductionmentioning
confidence: 97%
“…This may also lead to In-clustering and dots may be formed instead of a QW [6,7]. In spite of these problems the growth of ultrathin In-rich (UTIR) InXGa1−XN/GaN QWs having In composition of 60% -70% have been reported [8].…”
Section: Introductionmentioning
confidence: 97%
“…The results obtained are shown in Figs.3 -5. As depicted in these figures, for UTIR QWs the indium7 mole fraction corresponds to the as-grown indium concentration in InXGa1-XN layer, while in the case of dots it corresponds to the initial core concentration.Fig. 3shows the variation of the PL peak energies of as-grown and long annealed nanostructures (UTIR QWs and USIR QDs) with the BP for different indium concentrations corresponding to EC : EV = 83:17 and 68:32.…”
mentioning
confidence: 99%